2022
DOI: 10.3389/fpubh.2022.859819
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Lifestyle Behaviors and Sleep Quality Among Saudi Postmenopausal Women

Abstract: BackgroundOne of the most effective measures regarding improving women's health is to promote healthy lifestyle behaviors. This study aimed to investigate the relationship between health-promoting behaviors and sleep quality among a sample of Saudi menopausal women.MethodsA descriptive cross-sectional study was used to collect data from 410 Saudi postmenopausal women visiting primary healthcare care centers located in Sakaka, Jouf, Saudi Arabia, using the Menopause Rating Scale (MRS), Health-Promoting Lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Consistent with the current study, a previous study on middle-aged women showed a negative relationship between health-promoting behaviors and menopausal symptoms 20 . Health-promoting behaviors, regarded as protective factors, play a positive role in alleviating menopausal symptoms and improving health status 37,38 . The results suggest that promoting patients' health responsibility, stress management, and spiritual growth may mitigate treatment-induced menopausal symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the current study, a previous study on middle-aged women showed a negative relationship between health-promoting behaviors and menopausal symptoms 20 . Health-promoting behaviors, regarded as protective factors, play a positive role in alleviating menopausal symptoms and improving health status 37,38 . The results suggest that promoting patients' health responsibility, stress management, and spiritual growth may mitigate treatment-induced menopausal symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…20 Health-promoting behaviors, regarded as protective factors, play a positive role in alleviating menopausal symptoms and improving health status. 37,38 The results suggest that promoting patients' health responsibility, stress management, and spiritual growth may mitigate treatment-induced menopausal symptoms. However, a bidirectional relationship is likely to exist between health-promoting behaviors and menopausal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Walker and his colleagues have provided a comprehensive perspective on HPL [16], describing it as a multidimensional model of perceptions and actions, including health responsibility, physical activity, nutrition, interpersonal relations, spiritual growth, and stress management. Researchers have evaluated the level of HPL and its influencing factors in many different populations, such as older adults [17], university students [18], and postmenopausal women [19]. Some research have been conducted in people with physical diseases, such as cardiovascular and cerebrovascular diseases [20].…”
Section: Introductionmentioning
confidence: 99%
“…That implies that many women are at risk of lacking sleep for a long period. Lack of sleep increases the risk of chronic diseases such as hypertension, diabetes, and obesity, as well as the potential of comorbid anxiety and depression [5][6][7][8][9] , which is the leading cause of sedative medication in postmenopausal women, greatly increasing the economic burden [10] .…”
Section: Introductionmentioning
confidence: 99%